LAICITY AND WOMEN’S RIGHTS: EQUALITY AND DIFFERENCE IN CONTEMPORARY FRANCE - Portier, Philippe (Politikologija religije, 2015)
It is common practice to defend the idea that by separating, in 1880s-1905, the State from the Churches, in particular from the Roman Catholic Church, the French Republic has opened the way to the feminine emancipation. The return to the history tilts us to propose a more diffentiating interpretation. The influence of the laicity is, in France, by no means unambiguous: according to periods, the Republic adopted varied public policies towards women. This article presents a diachronic modelling, envisaged from the dialectic of the equality and the difference, of these policies. It spots a first period, 1880 till 1960, during which remains a hierarchical formula maintaining women in a status of inferiority ; between 1960 and 1990, the equality spouses with the religious difference; from 1990, under the influence of the controversy around the “ Muslim question “, France enter a more universalist model, in which the assertion of women’s rights comes along with a relative denial of the religious difference.